Influence of the urban vegetation on thermal dissipation and gaseous pollutants - Teresa Milagros Defilippi Shinzato; Alexis Dueñas; Julián Ccasani; Vanessa García; Gianinna Morales (Agathón)
In the urban environment, resilience is a result of the shocks caused by pollution, noise and changes in land usage, through the process of ‘artificialization’, typical of the process of building a city. Since the city is unthinkable without natural elements, therefore, it is important to study the tolerance to the ‘denaturalization’ urban system. The main objective of the article is to determine the benefits of urban vegetation on thermal dissipation and gaseous pollutants. From studies carried out in 13 parks located in Lima (Peru), from four monitoring stations (with or without vegetation), temperature, relative humidity, wind speed, and gaseous pollutants  are measured. The outcomes show significant differences on thermal dissipation and relative humidity, allowing to confirm that urban vegetation plays an important role in reaching increasingly sustainable levels at city scale.